KIF15 promotes the development and progression of chordoma via activating PI3K-AKT signalling pathway - Jinxing Yang; Lijun Liu; Xu Xu; Hui Zeng (Heliyon, 2024)
Aims: Despite its implication in various human cancers, the expression and functional significance of Kinesin family member 15 (KIF15) in chordomas remain unexplored. Main methods: The evaluation of KIF15 protein levels was conducted through immunohistochemistry (IHC) staining and Western blot analysis. Cell proliferation was quantified using MTT and CCK8 assays, whereas cell migration was examined using wound healing and Transwell assays. Furthermore, flow cytometric analysis was utilized to assess cell apoptosis and the cell cycle. Additionally, in vivo experiments were performed using a mouse xenograft model. Key findings: Our study revealed significantly higher expression of KIF15 in stage III chordoma tissues compared to stage II tissues. Knockdown of KIF15 led to notable inhibition of cell proliferation and migration, along with enhanced apoptosis and cell cycle arrest. In vivo studies further confirmed the inhibitory effects of KIF15 knockdown on chordoma tumour growth. In terms of mechanism, we identified the involvement of the PI3K-AKT signalling pathway mediated by KIF15 in chordomas. Notably, the anti-tumour effects of KIF15 deficiency on chordomas were partially reversed by the addition of an AKT activator. Significance: KIF15 promotes chordoma development and progression through the activation of the PI3K-AKT signalling pathway. Thus, targeting KIF15 might be a promising therapeutic strategy for treating chordomas.